2013
DOI: 10.1111/codi.12013
|View full text |Cite
|
Sign up to set email alerts
|

Result of the implementation of multidisciplinary teams in rectal cancer

Abstract: There was an improved postoperative mortality but no other potential benefits for the patients were seen after the implementation of colorectal MDTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 13 publications
1
31
0
5
Order By: Relevance
“…Surgery was performed 7-8 weeks after completion of chemoradiation. During the study period, multidisciplinary team meetings were implemented and all patients with rectal cancer discussed prior to surgery [14]. Patients in this study were not in an enhanced recovery programme.…”
Section: Methodsmentioning
confidence: 99%
“…Surgery was performed 7-8 weeks after completion of chemoradiation. During the study period, multidisciplinary team meetings were implemented and all patients with rectal cancer discussed prior to surgery [14]. Patients in this study were not in an enhanced recovery programme.…”
Section: Methodsmentioning
confidence: 99%
“…30 In general, these studies report higher rates of appropriate treatment, better adherence to clinical guidelines, and better survival. [31][32][33] In the current study, we have focused on these items as a measurement of the effects on patient care. We demonstrated that the administration of adjuvant chemotherapy in patients with high-risk stage II disease was significantly higher in those with SSR.…”
Section: Year Of Diagnosis Proportion Of Reports (%)mentioning
confidence: 99%
“…Nach dem PRISMA-Schema wurden 10 relevante Studien zu Auswirkungen von MDT auf das Überleben von Patienten identifiziert, die im skandinavischen Raum [27,28], den Niederlanden [29], Großbritannien und Schottland [30][31][32], den USA [33] [27,28,35], und eine Studie berichtet differenzierte Ergebnisse für beide Erkrankungen [33]. Die Anzahl der Beobachtungen reicht von 263 [35] bis hin zu 31 890 Patienten [29].…”
Section: Systematischer Review Und Metaanalyseunclassified